Struktur Teks dan Ideologi pada Wacana Berita Daring Bertema Pemilihan Gubernur DKI - Agus Hamdani; Filly Nova Vionita (Universitas Pendidikan Indonesia, 2022)
This article discusses the results of research on the structure of texts and ideologies contained in online news discourse with the theme of the election of the Governor of DKI Jakarta. The method used in this qualitative research is descriptive analytical method. The data sources are ten news discourses published by Kompas.com, Merdeka.com, and VIVAnews.com media in March and April 2017. The data were analyzed for text structure using van Dijk's theory of critical discourse analysis. The results show that the macro structure formed by journalists in news discourse with the theme of the election of the Governor of DKI Jakarta generally uses a frontal theme and tries to convince readers of what they write. The superstructure shows that journalists have provided systematic information according to their respective ideologies. The microstructure generally displays news content that influences public opinion, generates support, strengthens legitimacy, and eliminates opponents. The ideological representations contained in news discourse generally describe the legitimacy process of the dominant group against the minority group.